Ответы и объяснения

2014-03-11T09:54:58+04:00
-11+2d/3-d=-0,19/0,07                                                                                           (-11+2d)*0,07=(3-d)*-0,19                                                                                      -0,77+0,14d=-0,57+0,19b
0,14d-0,19d=-0,57+0,77                                                                                        -0,05d=0,2
d=-4
Лучший Ответ!
2014-03-11T10:04:34+04:00
А)-0,8х-2,9=-2,9+5,8х
-0,8х-5,8х=-2,9+2,9
-6,6=0
х=0
в)-3(2у-4)=7у-(-у-2)
-6у+12= 7у-у+2
-6у-7у+у=2-12
-12у=-10
у=1,2